Comparative Food Insecurities: Farmworker Perception of How the Quality and Quantity of Food Changes with Migration - Soper, Rachel (The International Journal of Sociology of Agriculture and Food, 2022)
Studies have found that farmworkers in U.S. agriculture report high rates of food insecurity. Yet scholars also point to hunger as the reason behind why farmworkers left their homes to come to the U.S. Thus, a binational comparison of food insecurity is needed. This study examines access to food prior to and after migration to California. Interviews with 40 farmworker households reveal that while respondents experienced more hunger in their home communities than they do in the U.S., the quality of food has decreased with migration. Respondents brought up the high quality of fresh, flavourful, organic food they grew themselves through natural methods. When the harvest ran out, without money to buy food, they experienced severe hunger. Some contrasted that to the abundance of food post-migration, and others discussed seasonal hunger during months when there is less work, yet all pointed to the low quality of food they have access to at U.S. grocery stores. With migration, respondents lost access to pesticide-free food. Rates of farmworker food insecurity miss the fact that even those who are considered food secure are not eating the quality of food they desire. A comparative perspective reveals the transformation of insecurity from insufficient amounts of fresh and natural food to increased consumption of food laden with chemicals. In neither context do the workers who harvest food for others have enough access to what they wish to be eating.